Ferulic acid depletion by cultured soybean seedlings under action of glucose and methionine - Herrig Vanessa; Silva Hélio Cândido da; Ferrarese Maria de Lourdes Lucio; Ferrarese-Filho Osvaldo (Brazilian Archives of Biology and Technology, 2000)
Cultured soybean seedlings were used to investigate how glucose or methionine influenced depletion of ferulic acid. Three-day-old seedlings were grown in hydroponic solution containing ferulic acid plus glucose or methionine, and the level of the phenolic acid were monitored in the nutrient culture. The results showed that ferulic acid depletion was more rapid in the presence of those compounds. After 6 h, the increase caused by glucose (0.01 and 0.05 mM) was more pronounced than methionine in the same concentrations. On the other hand, methionine (0.1 and 0.2 mM) increased depletion more significantly than glucose. Results suggested that both compounds might to increase the allelopathic effects of ferulic acid in the seedlings.